Balancing mathematics assessment tasks to accommodate problem-solving in Grade 7 classes - Bhekiswayo, Nomthandazo Moureen (University of the Free State, 2023)
The present South African mathematics curriculum, The Curriculum and Assessment Policy Statement, requires that learners be given the opportunity to acquire the ability to be systematic, generalise, solve problems, and think critically. These goals necessitate the use of assessment tasks that encourage learners' engagement in the development of mathematical thinking and reasoning. This means that teachers must exercise caution while designing assessment tasks and developing assessment strategies. Teachers must also be aware of the cognitive demands and nature of tasks and should include all in their assessment tasks. This study focused on to exploring how teachers balance mathematics assessment tasks to accommodate problem-solving and high-order cognitive demand in Grade 7. The model of mathematical task progression was adopted as a conceptual framework of this study. The selection of the model of mathematical tasks progression provided a lens through which the researcher could analyse the data and generate the empirical findings. The research followed a qualitative approach guided by a descriptive case study. The study was carried out in five schools, four township schools and a school in an urban area. Data were collected through semi-structured interviews, lesson observations document analysis. Social constructivism underpinned this study as it enabled the researcher to observe the participants in their own social settings. Through the use of thematic data analysis, the researcher was able identify themes. The findings revealed that teachers lack pedagogical content knowledge, that is, knowledge and skills in balancing their own assessments tasks; secondly, the study revealed that teachers excluded problem -solving in their assessment tasks as their understanding of problem-solving was limited; thirdly, teachers used textbooks as their source of assessment tasks and insufficient time was given to learners to work on tasks; fourthly, high-order questions were excluded during learning assessment and low-level cognitive demands were dominant in all the assessment tasks. Finally, teachers used only a teacher-centred approach and used teacher-learner dialogue as their teaching and assessment strategy. The challenges that emerged from the study had implications for assessment and thus required the assessment of mathematics in Grade 7 to be approached differently to enable learners to engage more in meaningful and balanced assessment tasks. Further training for teachers is needed in order to address the complexities that exist within the balancing of mathematics assessment tasks to include problem-solving.
Dissertation (M.Ed.(Mathematics Education))--University of the Free State, 2023
Keywords: Assessment strategies; Balancing; Cognitive demands; Mathematics tasks problem-solving; Teaching strategies